Socioeconomic disparities in children’s neurodevelopment before and during primary education: Evidence from Bagamoyo, Tanzania - Msilikale Walter Manyiri; Georg Loss; Susanne P. Martin-Herz; Deborah Sumari; Nicolaus Gutapaka; Thabit Athuman; Sylvester Simando; Sylvia Jebiwott; Xue Wu; Karim Manji; Ally Olotu; Michelle S. Hsiang; et al. (PLoS ONE, 2026)
Background Socioeconomic disparities in children’s neurodevelopment constitute a critical yet understudied developmental challenge in low- and middle-income countries (LMICs), yet longitudinal evidence from Sub-Saharan Africa (SSA) remains limited. This study aimed to evaluate the relationship between household wealth and neurocognitive trajectories in a cohort of Tanzanian children aged 6 months to 10 years. Methods We randomly selected 590 children aged 6 months to 10 years in Bagamoyo district, a low to moderate-malaria-endemic area in Tanzania. Participants completed comprehensive, age-appropriate neurodevelopmental assessments. The family’s socioeconomic status was derived from their household assets. Standardized, age-adjusted neurodevelopmental scores were regressed on socioeconomic status tertiles and by developmental periods: early childhood (6 months-3 years), preschool (4–5 years), and school age (6–10 years). Results While children from high- and low-Socioeconomic status (SES) families start with similar neurodevelopmental scores, a significant and sustained gap begins to emerge around age 2 years. This divergence results in a substantial disadvantage for children from the poorest households, with scores showing a difference of −0.36 Standard Deviation (SD) (95% CI: −0.64 to −0.08) during the preschool years and −0.41 SD (95% CI: −0.73 to −0.09) at school age. Conclusion Our results suggest that programs targeting the preschool period may be most effective in mitigating disparities in neurodevelopment.